Fatigue life prediction of composite material's adhesive joints in automotive applications. (2017) - Zhang, Wenlong; Tabiei, Ala
Composite and adhesive joints are used increasingly in the automotive industry, not only because of the government policy but also their advantages in mechanical properties over traditional materials and joints. An active research area is the fatigue analysis of adhesive joints. In this paper, a methodology to predict the fatigue life of adhesive joint is proposed and implemented into LS-DYNA with the joint modelled using a user-defined cohesive material. Fatigue crack growth rate is used to obtain the fatigue damage accumulation rate in cohesive zone model. Our method is verified by numerical simulations of two commonly used adhesive joints in the automotive industry: single-lap joint and stepped-lap joint. The predicted S-N curve fits well with the experimental data.